Feasibility of Radiofrequency Catheter Ablation in the Treatment of Atrial Fibrillation - Meshkova, M.; Doronin, A. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Atrial fibrillation (AF) is a worldwide epidemic that has hit about 33 million people. In clinical studies, the efficacy of antiarrhythmic therapy and catheter ablation in the treatment of AF was compared, and controversial results were obtained. Objective. To analyze three advanced publications in recent years, which, according to the authors, are of fundamental importance for the choice of radiofrequency catheter ablation as a treatment option for AF. Results and discussion. In the CABANA study catheter ablation was compared with antiarrhythmic therapy and showed significant improvement in the quality of life. Within 3 years, AF recurrence rate was 69% in the group of antiarrhythmic treatment and 50% in the catheter ablation group. The proportion of patients with non-paroxysmal AF decreased from 57% to 26% with antiarrhythmic treatment and up to 16% with catheter ablation. Among the serious complications in the catheter ablation group were tamponades (0.8%), minor hematomas (2.3%) and pseudoaneurysms (1.1%). Thyroid dysfunction (1.6%) and proarrhythmogenic effect (0.8%) were observed in the group of antiarrhythmic therapy. In the CASTLE-AF (HF) study, 179 patients were randomly selected for catheter ablation, and 184 for antiarrhythmic therapy. All of them were in NYHA class II, III or IV, had left ventricular ejection fraction 35% or less, and used implantable defibrillator. In the mean follow-up of 37.8 months, significantly less patients died after catheter ablation (24 [13.4%] versus 46 [25.0%]), and less were hospitalized due to worsening heart failure (37 [20.7%] versus 66 [35.9%]). ATTEST is the first randomized controlled trial that has demonstrated slowing down of the progression of AF after catheter ablation. Radiofrequency ablation was performed in 128 patients, antiarrhythmic therapy was applied in 127 patients. Within 3 years, the incidence of persistent AF or atrial tachycardia was lower in patients treated with ablation compared with patients on antiarrhythmic therapy (2.4% vs. 17.5%; P = 0.0009). Conclusions. The expected benefit of catheter ablation of AF in comparison with drug therapy is as follows: increase in the probability of maintaining sinus rhythm, improvement of the quality of life, decrease in the number of hospitalizations and all-cause mortality in patients with heart failure, decrease in fatigue.